2011
DOI: 10.1016/j.ijgo.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced maternal mortality in Tunisia and voluntary commitment to gender-related concerns

Abstract: The improvement in MMR can be credited to the voluntary political commitment focused on gender-related concerns that has been made in Tunisia, including access to family planning; legalization of abortion; and creation of the National Board for Family and Population, and the Tunisian Safe Motherhood initiative in 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…3860 The majority of studies (n=32) reported pregnancy-related deaths while three studies reported maternal deaths. 27,46,51 Studies were published in English, Spanish and Portuguese.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3860 The majority of studies (n=32) reported pregnancy-related deaths while three studies reported maternal deaths. 27,46,51 Studies were published in English, Spanish and Portuguese.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used reproductive-age mortality surveys (RAMOS) 26,27,38,45,53,59 and eleven studies used routine data from multiple sources such as local registries, hospital-based records, data of management information systems and/or by conducting interviews with health attendants. 29,30,44,46,49,51,52,54,55,58,60 Eight confidential enquiries into maternal deaths enumerated deaths from facility-based records.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…International documents and national studies have emphasized the effects of gender relations in reducing maternal deaths. In Tunisia, credit for improvements in maternal mortality ratio goes to a voluntary political commitment on gender related concerns, including access to family planning; legalization of abortion; the creation of the National Board for Family and Population, and the Tunisian Safe Motherhood initiative in 1999 (Farhat et al 2011). …”
Section: Factors Contributing To Maternal Deathsmentioning
confidence: 99%